Environmental Victimization: The Impacts of Transboundary Haze Pollution in Indonesia - Aisya, Naila Sukma; Gultom, Kardina; Susiatiningsih, Hermini; Farabi, Nadia (Journal of International Relations on Energy Affairs, 2024)
Forest fires and transboundary haze pollution have become annual problems faced by countries in Southeast Asia, especially in Indonesia, Malaysia, and Singapore. Since most of the burning forests occurred in Indonesia, the country has been accused to be responsible for the problems. Regarding this matter, the ASEAN member states have established the ASEAN Agreement on Transboundary Haze Pollution (AATHP). A major obstacle in combating the problems occurred as a result of the differences in interests between Indonesia and other ASEAN member states. Indonesia itself also faces complex domestic problems related to the conversion of forests and oil palm plantations. As a result, this problem continues to drag on and cause a great number of casualties and losses. This paper then seeks to analyze the problem of transboundary haze pollution in Indonesia and its impacts using the environmental victimization approach. The results show that the political discourses, both among ASEAN member countries and Indonesia's domestic affairs, have become stumbling blocks to effectively combating the problem. As a result, these problems resulted in casualties and caused legal and security, economic, health, social and cultural impacts.